PRINCIPLES OF CAPTURE BY FOREIGN LANGUAGE FROM THE POINT OF VIEW SOCIAL CULTURAL PARADIGM - Litovca, Т. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The question of correlation of language and culture is examined in the article, linguistic functions during the process of intercourse, establishment of social linguistic conformities to the law of functioning of language in different spheres of culture are determined. As a study of foreign languages goes out outside an only didactic process, a foreign language must be taught and as a mean of opening of other cultural world, and from the point of view development of social cultural paradigm of man in the process of its co-operation with the representatives of foreign cultural association.